Assessment of aromatic plant resistance to cadmium heavymetal through analysis of growth and physiology. Issue 1 (1st June 2022) - Sulastri, Y S; Sabrina, T; Mukhlis,
Abstract: Information about the resistance of aromatic plants to heavy metals is still little, so related research is needed. This study uses Factorial Block Random Design; Factor I: aromatic plant type T1=vetiver grass, T2=citronella grass, T3=lemongrass, T4=patchouli, T5=basil; Factor II: concentration of Cd (K0=0 ppm, K1=85 ppm, K2=170 ppm, K3=255 ppm, K4=340 ppm) where each treatment is repeated 3 times. The observed parameters are root dry weight, shoot dry weight, the substance of chlorophyll a/b, and total chlorophyll. As the results, citronella grass can be selected as candidates for cadmium heavy metal phytoremediation plants because citronella grass has root dry weight and shoot dry weight highest than the others. In addition, vetiver grass can be proposed as a means of phytoremediation because it shows growth physiology responses better under Cd pressure where the dry weight of the roots and shoots increases by 32.48% and 37.95%; total chlorophyll increases by 5.80%. Basil can also be selected because it shows growth and physiology responses better under Cd pressure where the dry weight of the roots and shoots increases by 18.90% and 97.92%; chlorophyll a, chlorophyll b and total chlorophyll increases by 4.08%, 4.36%, 5.88% respectively.